PENERAPAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV DI SD MUHAMMADIYAH 3 SURABAYA PADA MASA PANDEMI COVID-19 - Yuliyana Yuliyana; Kunti Dian Ayu Afiani; Ishmatun Naila (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2022)
This study aims to improve student learning outcomes in thematic learning by applying learning videos. The research subjects were the students of class IV.B SD Muhammadiyah 3 Surabaya City from odd semester in academic year of 2021/2022 with a total 25 students. The instrument used was the form of learning outcomes test, student activity test and teacher management test in learning. Based on the results of the study, the increase in learning outcomes with the percentage of classical learning completeness in cycle I and cycle II were 60% and 88%, respectively. The results of observing student activities obtained and increase in the average percentage of cycle I dan cycle II was around 70% and 75%. The results from observations of teacher management in learning is increase in the average percentage of cycle I and cycle II were 71% and 78%, respectively. From the results of this study, it can be concluded that learning videos can improve student learning outcomes.